2013
DOI: 10.1186/2050-7283-1-30
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the cogstate brief battery in identifying cognitive impairment in mild cognitive impairment and Alzheimer’s disease

Abstract: BackgroundPrevious studies have demonstrated the utility and sensitivity of the CogState Brief Battery (CBB) in detecting cognitive impairment in Alzheimer’s disease (AD) and mild cognitive impairment (MCI) and in assessing cognitive changes in the preclinical stages of AD. Thus, the CBB may be a useful screening tool to assist in the management of cognitive function in clinical settings. In this study, we aimed to determine the utility of the CBB in identifying the nature and magnitude of cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
193
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(209 citation statements)
references
References 47 publications
11
193
1
4
Order By: Relevance
“…Although smaller effects of 34 carriage on Ab-related cognitive decline were observed for attention and psychomotor function, no statistically significant effect of 34 carriage was evident for Ab-related rates of change on the CDR sum of boxes or MMSE. These data show that even with the larger sample size, these instruments do not have sufficient sensitivity to detect the cognitive effects of 34 in Abþ older adults (Table 1) (Gomar et al, 2014;Lim et al, 2013;Okonkwo et al, 2014) most likely because cognitively normal adults continue perform at, or around, ceiling levels. This characteristic also means that data distributions for both instruments do not meet necessary statistical assumptions for parametric data analyses (e.g., normality and equality of variance), thus limiting further their utility for characterizing cognitive change preclinical AD.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Although smaller effects of 34 carriage on Ab-related cognitive decline were observed for attention and psychomotor function, no statistically significant effect of 34 carriage was evident for Ab-related rates of change on the CDR sum of boxes or MMSE. These data show that even with the larger sample size, these instruments do not have sufficient sensitivity to detect the cognitive effects of 34 in Abþ older adults (Table 1) (Gomar et al, 2014;Lim et al, 2013;Okonkwo et al, 2014) most likely because cognitively normal adults continue perform at, or around, ceiling levels. This characteristic also means that data distributions for both instruments do not meet necessary statistical assumptions for parametric data analyses (e.g., normality and equality of variance), thus limiting further their utility for characterizing cognitive change preclinical AD.…”
Section: Discussionmentioning
confidence: 77%
“…The current finding that APOE 34 increased Ab-related memory decline is consistent with the interactions between 34 and Ab on memory observed in cross-sectional studies. For example, although large cross-sectional studies of preclinical AD find that high Ab is not associated with cognitive impairment (Doraiswamy et al, 2012;Lim et al, 2013), Ab burden is associated weakly with memory performance when samples are limited to Abþ individuals who also carry the APOE 34 allele (Kantarci et al, 2012;Lim et al, 2013). Taken together, these data do suggest that 34 does influence the effects of Ab on cognition, although the nature of this effect is relatively subtle and seen most clearly from prospective study of relatively large samples of Abþ individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a pool of 12 randomized trials comparing donepezil with placebo showed a mean difference of À1.969 at 12 weeks and À2.895 at 24 weeks [48]. The CogState computerized cognitive testing is a more recent tool which consists of four cognitive tasks involving playing cards [49,50]. In this battery of tests, the test taker is provided instructions on a computer screen and responds using a computer keyboard with a 'yes' or 'no' answer based on a certain rule.…”
Section: Clinical Efficacy In Admentioning
confidence: 99%